Toxicity-guided assessment of disinfection by-products via machine learning and network toxicology - Jie Wang; Zhujun Liu; Ruipeng Lai; Xianyu Song; Yukun Zhang; Shuangliang Zhao; Honglai Liu (Water Research, 2026)

ALOX15 exerts tumor-suppressive role in head and neck squamous cell carcinoma via ERK pathway - Aoran Liu; Xinyue Zhang; Ruipeng Li; Yuzhe Zhang; Ziyi Yang; Dan Zou; Xu Ji; Hong Li (Functional & Integrative Genomics, 2026)

Structure-resolved adsorption of PFAS on humic substances: A combined study of molecular dynamics, explainable machine learning, and experiments - Yuxiang Nie; RuiPeng Lai; Huaicheng Bei; Xianyu Song; Dan Liu; Limeng Yin; Shuangliang Zhao; Honglai Liu (Chemical Engineering Journal, 2026)

Numerical investigation of thermodynamic cavitation dynamics over a hydrofoil incorporating surface tension and viscous effects - Weixiang Ye; Ruipeng Wang; Hao Liu; Wenkui Ma; Xianwu Luo (Ocean Engineering, 2026)

Enhanced mechanical properties of concrete with 3D corrugated auxetic lattices - Yongpeng Lei; Ruipeng Liu; Xinjuan Zhao; Hui Wang (Engineering Structures, 2026)

Compressive behavior of a novel 3D auxetic lattice reinforced ice-based composite: Experiments and modeling - Ruipeng Liu; Yongpeng Lei; Zhu Liu; Tianhui Hao; Hui Wang; Haotian Guo (Cold Regions Science and Technology, 2026)

Improved remediation mechanism of groundwater circulation wells based on ultrasonic permeability enhancement - Yan Zhao; Liu Yang; Siyuan Li; Mingxiu Ji; Ruipeng Dong (Process Safety and Environmental Protection, 2026)

Quantitative effects of substrate, vegetation, and hydraulic loading on pollutant removal in constructed wetlands - Gongliang Zhang; Qing Li; Ran Cai; Guozhu Mao; Ruipeng Miao; Miaomiao Liu; Dexiang Li; Chenxin Song (Ecological Engineering, 2026)

Mechanism of direct-push injection impact on porous media structure and contaminant removal performance - Mingxiu Ji; Ruipeng Dong; Liu Yang; Shupei Wu; Yan Zhao (Journal of Contaminant Hydrology, 2026)

Dual aggregation steering in bulk-heterojunction via solvent engineering toward efficient and stable binary organic solar cells - Yijing Lin; Bing Zheng; Xingting Liu; Huizhen Xu; Liyang Yu; Ruipeng Li; Xin Song; Weiguo Zhu (Chemical Engineering Journal, 2026)

Strength Deterioration Mechanism of Sandstone Subjected to Low-Frequency Dynamic Disturbance Under the Varying Static Pre-stress Levels - Xiaoze Wen; Guorui Feng; Jun Guo; Ruipeng Qian; Wenming Feng; Jinwen Bai; Kenan Liu; Xu Zhang; Daniel Dias (Rock Mechanics and Rock Engineering, 2026)

Emulsion coating: One-pot method preparing the sealable microporous surfaces with antibacterial and antithrombotic properties - Jingze Liu; Yueze Hong; Yao Xiong; Yage Hu; Jiaqi Wang; Yuan Wei; Tong Wang; Haichao Yu; Ruipeng Xue; Li Yang; Gaocan Li; Rifang Luo; et al. (Chemical Engineering Journal, 2025)

Defect-mediated permeation of deep eutectic solvents in cellulose crystals: A combined experimental and molecular dynamics study - Yuanhong Yu; Xianyu Song; Yanglong Wang; RuiPeng Lai; Yuxiang Nie; Wenjun Xiang; Chuxiang Zhou; Shuangliang Zhao; Honglai Liu (Carbohydrate Polymers, 2025)

Research on the in-situ permeability enhancement mechanism of loose porous medium using ultrasonic waves based on NMR - Yan Zhao; Liu Yang; Siyuan Li; Shengke Yang; Zhenkun Geng; Mingxiu Ji; Ruipeng Dong; Yinyu Wen (Journal of Hydrology, 2025)

Impact of the potassium transporter TaHAK18 on wheat growth and potassium uptake under stressful K+ conditions - Tengfei Liu; Yanan Zhang; Yumin Xie; Ruipeng Yang; Mengying Yuan; Yanke Li; Haixia Xu; Xinli Zhu; Tengzhao Song; Xiyong Cheng (Journal of Plant Physiology, 2025)

Effect of water intrusion on mechanical behaviors and failure characteristics of backfill body and coal pillar composite specimens under uniaxial compression - Ruipeng Qian; Xiaoli Liu; Qing Ma; Guorui Feng; Jinwen Bai; Jun Guo; Shuai Zhang; Xiaoze Wen (Journal of Cleaner Production, 2025)

December 2022 north American bomb cyclone: Insights from perturbation energetics - Emerson DeLarme; Jianping Li; Hongyuan Zhao; Yuan Liu; Ruipeng Sun (Atmospheric Research, 2025)

Synthesis of PbCrO4 nanorods-Ti3C2Tx MXene composites: A sensitive photoelectrochemical sensor for the detection of cysteine in human blood serum - Wenbo Lu; Yupeng Wang; Siyu Liu; Wanyu Xie; Ming Wei; Ruipeng Hao (Analytica Chimica Acta, 2025)

Effect of co-fermentation of Rhodotorula mucilaginosa with Saccharomyces cerevisiae on the quality and flavor profile of cider - Shijiao Liu; Ruipeng Wang; Yunong Zhang; Yiwei Dai; Sufang Zhang; Xinping Lin; Chaofan Ji; Huipeng Liang; Yingxi Chen (Food Bioscience, 2025)

Applicability of soil health assessment dominated by biological indicators in facility agriculture - Hao Su; Zhihan Yang; Zhenyu Liu; Ruipeng Zhang; Sixuan Wu; Yaying Li; Huaiying Yao (Science of The Total Environment, 2024)

Progressive failure processes and mechanisms of disasters caused by interrelated failure of residual coal pillars and rock strata - Qing Ma; Xiaoli Liu; Ruipeng Qian; Yunliang Tan; Bing Qiuyi Li; Xuesheng Liu (Science of The Total Environment, 2024)

Chalcogen effect on the photovoltaic performance of nonfused-ring small molecular electron acceptors for efficient organic solar cells - Siyang Liu; Xiaowei Chen; Yinfeng Li; Xiaopeng Xu; Liyang Yu; Yuwei Duan; Ruipeng Li; Qiang Peng (Chemical Engineering Journal, 2024)

Simultaneously improved Jsc and Voc achieving 19.15% efficiency in ternary blend polymer solar cell containing a Y-type acceptor with thiophene based end groups - Guangjun Zhang; Qingxing Wu; Yuwei Duan; Wanqiang Liu; Min Zou; Hu Zhou; Jiamin Cao; Ruipeng Li; Xiaopeng Xu; Liyang Yu; Qiang Peng (Chemical Engineering Journal, 2023)

Terpenoids of quinoa bran suppresses colorectal cancer by inducing cell apoptosis - Man Ding; Xuechen Zhang; Jiangying Shi; Kaili Cui; Ruipeng Yang; Fengming Liu; Shuhua Shan; Ghani Israr; Zhuoyu Li (Food Bioscience, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Numerical investigation on mechanism and fluid flow behavior of goaf water inrush: a case study of Dongyu coal mine - Xiaohong Niu; Guorui Feng; Qin Liu; Yanna Han; Ruipeng Qian (Natural Hazards, 2022)

A Manta Ray Robot with Soft Material Based Flapping Wing - Qimeng Liu; Hao Chen; Zhenhua Wang; Qu He; Linke Chen; Weikun Li; Ruipeng Li; Weicheng Cui (Journal of Marine Science and Engineering, 2022)
Recent research on robotic fish mainly focused on the bionic structure design and realizing the movement with smart materials. Although many robotic fish have been proposed, most of these works were oriented toward shallow water environments and are mostly built with purely rigid structures, limiting the mobility and practical usability of robotic fish. Inspired by the stability of the real manta ray, a manta ray robot design is proposed with soft material made flapping wing based on an open-source ROV (Remotely Operated Vehicle). The flapping wing structure with three different materials mimics the wide pectoral fins of real manta rays, which have bones, muscles, and skin. Furthermore, its modular design makes it easy to install and disassemble. The kinematic and hydrodynamic analysis of the manta ray robot are simulated in this paper. The actual manta ray robot is fabricated and several sets of test are performed in the pool. The robot can swim forward continually and stably with a simple rolling and pitching pattern.

Quantitative health risk assessment of inhalation exposure to automobile foundry dust - Ruipeng Tong; Mengzhao Cheng; Xiaofei Ma; Yunyun Yang; Yafei Liu; Jianfeng Li (Environmental Geochemistry and Health, 2019)

Genetic parameters for growth and survival traits in Litopenaeus vannamei at different ages - Jiachen Zhang; Fujun Cao; Jianyong Liu; Ruipeng Yuan (Aquaculture International, 2017)